Takayasu arteritis in pregnancy: case report of two cases and review of literature - Rengaraj, Sasirekha; Rani, P. Reddi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Takayasu arteritis is a rare medical disorder of unknown etiology. The primary vasculitis mainly affects women of reproductive age group. Even though the usual course is slow, sometimes it may be unpredictable. It usually involves the branches of the aortic arch. With advancement of medicine most of the patients enter pregnancy with the disease already being diagnosed and on medications. Even though pregnancy is a favourable state complications are bound to happen especially when the disease is diagnosed for the first time during pregnancy. We are presenting two cases of Takayasu arteritis during pregnancy with different clinical presentations.